Pedagogical Competence of Teachers in Integrating Science and Technology in Early Childhood Education: A Case Study of Raudhatul Athfal in Rappocini District, Makassar - NURHIDAYA, ANDI REZKY; Azisah, St; Ibrahim, Misykat Malik; Rahman, Ulfiani (Journal of Research and Multidisciplinary, 2024)
This dissertation aims to: (1) Describe teachers' pedagogical competence at Raudhatul Atfhal in designing and implementing educational activities using Science Technology Society (STS); (2) Analyze the use of technology and communication through STS; (3) Evaluate students' learning outcomes based on teachers' pedagogical competence. This qualitative research uncovers the pedagogical competence of RA teachers in applying STS, using observations, interviews, and documentation. Four teachers from RA Mardhati and Hasirah Home School participated. Data analysis followed steps of condensation, presentation, and conclusion. Findings show that RA Mardhati and Hasirah teachers demonstrate strong competence in planning, implementing, utilizing ICT, and evaluating learning outcomes. Teachers at RA Mardhati create supportive and dynamic learning environments, while Hasirah teachers plan structured lessons through daily and weekly plans. The use of ICT (e.g., Wi-Fi, laptops) enhances the learning process, making it more engaging and interactive. Teachers evaluate learning daily and report progress comprehensively, focusing on both process and outcomes. The implications emphasize the need for continued development of pedagogical competence. RA institutions should support teacher training to adapt teaching methods to students' needs. Teachers are encouraged to enhance professionalism through external training. Future research should explore deeper variations of methods to provide a more comprehensive understanding of pedagogical competence at RA.